TINJAUAN KUALITAS FASILITAS WISATA DI PANTAI GANDORIAH KOTA PARIAMAN - Rita, dEFFI Faffua; Chair, Ira Meirina; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2015)
The purpose of research is to describe quality of tour facility at Pantai Gandoriah Kota Pariaman. This research consists of five indicators are: transportation facility, accommodation facility, food and beverage facility, object and attraction, and shopping facility. Type of this research is descriptive using qualitative and quantitative. Data in this research reviewed by primary data, are: 1). Chairman of tour facility department Dinas Kebudayaan dan Pariwisata Kota Pariaman and tour facility organizer using interviewed, 3) tourist that visit to Pantai Gandoriah using questionnaire. That applying purposive sampling technic. Based on the results of the study showed quality of tour facility at Pantai Gandoriah Kota Pariaman at category sufficiently with skor distance 126 - < 154 and interpretation 38%. Regards : Tour Facility, Pantai Gandoriah